Global groundwater: from scarcity to security through sustainability and solutions - Mukherjee, A.; Scanlon, Bridget R.; Aureli, A.; Langan, Simon J.; Guo, H.; McKenzie, A. (Elsevier, 2021)
Groundwater, the largest available global freshwater resource, plays a crucial role in human sustenance and global food security through drinking water supplies and irrigated agriculture. In recent times, many parts of the world have been experiencing discernable, large-scale groundwater depletion, and pollution. A large groundwater-dependent population, uncertain climate-reliant recharge processes, transboundary water sources, major geogenic-sourced, nonpoint contaminants, inefficient irrigation methods and human practices, and indiscriminate land use change with rising urbanization underscore the urgent need to develop models of sustainability and security for global groundwater, in terms of both quantity and quality. Climate change is expected to exacerbate these issues. We need to understand the main factors that control groundwater availability (quantity and quality) in a changing world, where climate change and human factors (overexploitation, pollution, economics, agro-food aspects and their socioeconomic side, and governance intervention) deeply influence water availability. Because groundwater represents a critical source of water in many areas, especially in developing countries, there is a need to analyze physical (hydrological), chemical (hydrogeochemistry), and human (socioeconomic) aspects within a comprehensive framework to define sustainability. Groundwater, which forms a large component of attaining the sustainable development goals, is difficult to manage (mostly not visible, limited monitoring of groundwater levels, recharge, and abstraction, poorly defined flow boundaries; transboundary issues; poor management of abstraction; uncertainty in groundwater–surface water inter-connections) and hence requires comprehensive scale–dependent governance plans. From an economic and governance point of view, there has been insufficient attention given to groundwater as a resource, which is both hidden but widely considered ubiquitous. Solutions, incorporating emerging and innovative technologies, need to be integrated with traditional knowledge, to develop future groundwater security.